Ngā Whakāwhitinga (standing at the crossroads): How Māori understand what Western psychiatry calls "schizophrenia". (April 2018) - Taitimu, Melissa; Read, John; McIntosh, Tracey
This project explored how Māori understand experiences commonly labelled "schizophrenic" or "psychotic". Semi-structured interviews were conducted with 57 Māori participants who had either personal experiences labelled as "psychosis" or "schizophrenia", or who work with people with such experiences; including tangata whaiora (users of mental health services), tohunga (traditional healers), kaumatua/kuia (elders), Māori clinicians, cultural support workers and students. Kaupapa Māori Theory and Personal Construct Theory guided the research within a qualitative methodology. The research found that participants held multiple explanatory models for experiences commonly labelled "psychotic" or "schizophrenic". The predominant explanations were spiritual and cultural. It seems that cultural beliefs and practices related to mental health within Māori communities remain resilient, despite over a century of contact with mainstream education and health services. Other explanations included psychosocial constructions (interpersonal trauma and drug abuse), historical trauma (colonisation) and biomedical constructions (chemical brain imbalance). Participants (both tangata whaiora and health professionals) reported they were apprehensive about sharing their spiritual/cultural constructions within mainstream mental health settings due to fear of being ignored or pathologised. This study highlights the importance of asking users of mental health services about the meaning they place on their experiences and recognising that individuals can hold multiple explanatory models. Māori may hold both Māori and Pākehā (European) ways of understanding their experiences and meaningful recognition should be afforded to both throughout assessment and treatment planning in mental health services. Clinicians need to be aware that important personal and cultural meanings of experiences labelled psychotic may be withheld due to fear of judgement or stigmatisation.